2023
DOI: 10.1039/d3dt02896h
|View full text |Cite
|
Sign up to set email alerts
|

A robust Zintl cluster for the catalytic reduction of pyridines, imines and nitriles

Bono van IJzendoorn,
Jessica B. M. Whittingham,
George F. S. Whitehead
et al.

Abstract: A boron functionalized phosphorus Zintl cluster was employed to catalytically hydroborate N-containing substrates. The catalyst could be recycled 9 times without loss in performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…Later, we reported the same cluster as an active catalyst in the hydroborative reduction of pyridines, imines, and nitriles. 25 We also demonstrated that a range of Zintl ions and phases could initiate the hydrophosphination of HPPh 2 across alkynes, alkenes, and imines. 26 Also in 2022, we prepared a metal-free heptaphosphane cluster with borane moieties linked via an aliphatic chain, ({C 8 H 14 }BCH 2 CH 2 SiMe 2 ) 3 P 7 (1).…”
Section: ■ Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Later, we reported the same cluster as an active catalyst in the hydroborative reduction of pyridines, imines, and nitriles. 25 We also demonstrated that a range of Zintl ions and phases could initiate the hydrophosphination of HPPh 2 across alkynes, alkenes, and imines. 26 Also in 2022, we prepared a metal-free heptaphosphane cluster with borane moieties linked via an aliphatic chain, ({C 8 H 14 }BCH 2 CH 2 SiMe 2 ) 3 P 7 (1).…”
Section: ■ Introductionmentioning
confidence: 70%
“…In this 2022 work, the synthesis of a boron-functionalized [P 7 ] cluster was reported and found to facilitate the reduction of CO 2 to a methoxyborane with high activity and complete selectivity. Later, we reported the same cluster as an active catalyst in the hydroborative reduction of pyridines, imines, and nitriles . We also demonstrated that a range of Zintl ions and phases could initiate the hydrophosphination of HPPh 2 across alkynes, alkenes, and imines …”
Section: Introductionmentioning
confidence: 74%
“…Again, the greatest conversion was obtained when pyridine was employed as the solvent. Consistent with our previous report, when the unfunctionalized [Na(DME) x ] 3 [P 7 ] cluster was tested in the hydroboration of pyridines, imines, and nitriles, 21 addition of 18-c-6 improved conversion with complete consumption of 2a obtained within 15 min (12 h without 18-c-6). We postulate that the cation sequestering agent increases the solubility of the anionic species, increasing the effective loading in solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2022, we reported the first example of Zintl transition metal-free catalysis, when the boron-functionalized cluster [Na­(18-c-6)] 2 [(BBN)­P 7 ] ( 1 ) (also studied in this report) was found to facilitate the reduction of CO 2 to a methoxyborane. Later, we reported the same cluster as an active catalyst for the hydroboration of pyridines, imines, and nitriles . We also prepared the boron-tethered [P 7 ] cluster where the cluster and boron are linked via an aliphatic unit to mediate hydroboration catalysis; however with this system, the cluster is an innocent platform for boron catalysis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation